Epithelial Ovarian Cancer: The Importance of Early Diagnosis and Individualized Treatment with Combination Chemotherapy and Targeted Therapy - Franco, Ana Clara Rodrigues; Batista, Maria Gabriella Cunha; Rezende, Eduardo Henrique Mendes; Filho, Murilo Dell Eugenio Costa; Schimin, Mayra Algeri; Filho, Durval José dos Santos; Segundo, Raylton Jansen e Silva; Araújo, Lucas Torres de; Alves , Natana Carol; Pinheiro, Bruno Barbosa (Brazilian Journal of Implantology and Health Sciences, 2024)
Epithelial ovarian cancer is a malignant neoplasm that represents the majority of ovarian cancer cases. It is characterized by aggressiveness, often late diagnosis and therapeutic challenges. Early diagnosis is crucial to improving patients' survival rates and quality of life. Individualized treatment, combining chemotherapy and targeted therapy, has been a promising approach to optimize therapeutic results and minimize adverse effects. Objective: to analyze and synthesize the available evidence on the importance of early diagnosis and individualized treatment with combined chemotherapy and targeted therapy in epithelial ovarian cancer. Methodology: Using the PRISMA checklist, this review was conducted based on articles published in the last 10 years. The databases used were: PubMed, Scielo, Web of Science. The descriptors: "epithelial ovarian cancer", "early diagnosis", "individualized treatment", "combined chemotherapy", "targeted therapy". Inclusion criteria: original studies in humans, published in English or Portuguese, addressing the early diagnosis and/or individualized treatment of epithelial ovarian cancer. Exclusion criteria: animal studies, systematic reviews, studies with non-representative samples. Results: The results of this review highlight the importance of early diagnosis through imaging techniques and tumor markers. Furthermore, they highlight the effectiveness of combination chemotherapy, especially regimens containing platinum and taxanes, together with targeted therapy, such as PARP inhibitors, in improving response rates and survival in patients with epithelial ovarian cancer. Conclusion: Early diagnosis and individualized treatment with combination chemotherapy and targeted therapy play a key role in the management of epithelial ovarian cancer. This multifaceted approach can significantly improve patients' clinical outcomes and quality of life, highlighting the importance of personalized therapeutic strategies in this challenging clinical context.